Phenological behavior and agronomic potential of blackberry and hybrids in a subtropical region - Copello Rotili, Maria Cristina; Villa, Fabíola; Fernandes da Silva, Daniel; Rosanelli, Solivan; Menegusso, Fernanda Jaqueline; Ritter, Giovana (Revista Ceres, 2025)
The purpose of this study was to evaluate the phenological behavior and agronomic potential of blackberry varieties and hybrids in a subtropical region. Blackberry seedlings of four varieties and two hybrids were purchased in April 2015 in the form of stem cuttings and transplanting in July 2015. Winter pruning was carried out on August 18, 2016 and 2017. The experimental design was composed of a randomized complete block design, containing four varieties and two hybrids, four blocks and five useful plants per experimental unit. The harvest was performed every two days to the determination of fresh biomass, longitudinal and transverse diameter, volume, number of fruits per plant, yield and estimated productivity. The average duration of the phenological cycles in the two harvests varies between 109 and 162 days and 114 and 148, respectively. Hybrids Boysenberry and Olallie presented a shorter cycle in both harvests. In the 2016/2017 crop, the harvest lasted from 39 to 88 days. In the 2017/2018 harvest, it lasted 23 to 57 days, starting in mid-November through early January. The Tupy and Chickasaw cultivars were the most productive in the first crop. In the second crop, the Tupy and Navaho cultivars were prominent.